PERENCANAAN ARTIFICIAL REEF SEBAGAI RESTORASI TERUMBU KARANG DAN PENGAMAN PANTAIDI PULAU LEMUKUTAN KABUPATEN BENGKAYANG - Dhiecho Mahar Dhiecha (Jurnal Teknologi Lingkungan Lahan Basah, 2015)
ABSTRACT Damage that occurs around the area Lemukutan Island caused the use of chemicals or cyanide to catch fish and coral reefs by local people, but it is also often made use of bombs surrounding communities to take beautiful corals that will be sold to destroy coral reef ecosystems in the waters .Artificial reef planning methods (Artificial reef ) as the restoration of coral reefs and coastal protection is to conduct a field survey using a measuring instrument GPS topographic, marine water quality data and using secondary data, statistical data, tidal, wave height, bathymetry map, direction of flow and wind direction. Water quality analysis carried out in-situ, parameter test in the brightness of the water, currents, salinity, temperature, pH. Analysis of the function of Artificial reefs for reef restoration and as coastal protection is to use a hollow dome type or reef balls. Appropriate placement location and located at coordinates N 00 45 '33.8 ", E 1080 42' 19.5" up to N 00 45 '29.2 "E 1070 15' 49.0", and the average depth of 3 meters. Results of water quality testing based on parameters salinity, current velocity, pH, turbidity, light intensity and temperature qualify coral life quality standards in Indonesia based on PERMEN LH No. 51 TAHUN 2004. The dimensions of Artificial reef s diameter of 1.80 m, height 1.50 m with a thick layer of 10 cm and a hole located on the sides of the Artificial reef for 34 holes with a diameter of 15 cm. Filler material used is concrete with a volume of 0.916 m3, equivalent to 2,198 tons. Binder or cement used type V, which is resistant to high sulfate levels. The amount of reef balls used is 834 pieces. Keywords: Artificial reef , Seawater Quality, Reef balls and coral reefs,.